Predictors of selection into an elite level youth football academy: A longitudinal study - Fortin-Guichard, D.; Huberts, I.; Sanders, J.; van Elk, R.; Mann, D. L.; Savelsbergh, G. J. P. (Journal of Sports Sciences, 2022)
Talent identification in football is complex. Research regarding talent indicators that predict selection into professional academies is increasingly multi-disciplinary, though is typically cross-sectional, failing to consider whether the rate of change of those indicators influences selection. The aim of this study was to determine if longitudinal changes in talent indicators are associated with selection into a professional football academy. A total of 110 Dutch male football players (aged 8-12) playing in a youth development programme of a professional club were included in the study. Players were assessed regularly on their anthropometry, physical fitness, gross motor coordination, technical ability, and psychosocial capacities over four years. A subset of players was then selected into the academy. Cross-sectional and longitudinal analyses revealed the indicators that best predicted selection. The best indicator was the 30 m sprint speed, with prediction not improving when including other predictors or their rate of change. The individuals that the club ultimately selected at age 12 could have been predicted well above chance levels using the sprint speeds at age nine or ten. The relative consistency of the rate of improvement in indicators across participants meant that the rate at which they developed played little role in selections.